The dissociation between pathological caloric testing and a normal video head impulse test helps differentiate between Menière’s disease, vestibular migraine, and other vestibular disorders: a confirmatory study in a large cohort of 2,101 patients - Mavrodiev, Vergil; Strupp, Michael; Vinck, Anne-Sophie; van de Berg, Raymond; Lehner, Louisa (Frontiers in Neurology, 2024)
Vestibular migraine (VM) and Menière's disease (MD) are characterized by episodes of vertigo of similar duration. It is well known that the differentiation between both diseases is not always possible based only on the patient history, physical examination and audiological testing. In addition, the quantification of the vestibular function can also be helpful since, among patients with MD, there is often a dissociation between a normal/pseudo-normal video head impulse test (vHIT) and reduced caloric testing. The goal of this confirmatory study was to determine the sensitivity, specificity, and positive and negative predictive values (PPV and NPV) of this dissociation to differentiate between MD and VM as well as between MD and other vestibular diseases.We performed a retrospective analysis of 2101 patients. The examination group consisted of 1100 patients; 627 (57%) with MD according to the diagnostic criteria of the Bárány Society and 423473 (43%) with VM. The comparison group consisted of 1001 patients with other peripheral, central, or functional vestibular disorders.Statistical analysis revealed for the dissociation the following findings: